Toxigenic Fungi in Food - Davis, N. D. (1975)
Forty-five fungal isolates from moldy supermarket foods were tested for toxicity to brine shrimp, and twenty-two of these isolates were subsequently tested for toxicity to chicken embryos. Highly toxigenic fungi were Cladosporium sphaerospermum from a bakery product, Fusarium oxysporum from carrots, F. solani from cabbage, Aspergillus niger and Penicillium corylophilum from bread, P. cyclopium and P. herquei from corn meal, P. lanosum from onions, P. steckii from chocolate syrup, Penicillium sp. from jelly, and Rhizopus nigricans isolates from sweet potato, applesauce, and strawberries. Approximately one-third of the fungal cultures were moderately to highly toxigenic to brine shrimp and chicken embryos, while several additional cultures were slightly toxigenic.